Panic button app - Dee, Robert Isaac; Dorado, Dan Anthony; Enriquez, Paul Michael; Estacio, Rogelio Jr.; De Guia, Josefa; Gonzales, Ping.; Laspinas, Rhea.; Macalintal, Anna Lynn.; Malonzo, Nur Ishmael; Maquito, Rommel; Obille, Ma. Elisa; Santos, Edward; et al. (University of the Philippines Diliman, Quezon City Technology Management Center, 2014)
The class was tasked to come up and implement a project using the concepts of Project Management. The group, which calls its company TBD Solutions, chose to come up with a project that aims to leverage on better multi-stakeholder partnerships to have a more disaster and emergency-ready community. This is because the Philippines is considered to be an emergency and disaster-prone country. Despite the comprehensive National Disaster Risk Reduction and Management Plan, regions, cities, organizations and firms in the country might still have various non-unified efforts towards preparing for and responding to emergencies. There is an urgent need for the country to work together through multi-stakeholder partnerships and robust institutional mechanisms and processes so that Filipinos will be able to live in safer, adaptive and disaster resilient communities. The Panic Button App is TBD Solutions' answer to the Filipino's urgent need for a better, quicker and more efficient emergency response system. It will act as a bridge to the nation's emergency responders, bringing them within reach of the average Filipino and putting them in a position to respond to emergencies in a timely manner. With the push-of-a-button, the app will send alert messages containing the sender's location and status to intended recipients for swift emergency response. The Panic Button App will create revenues through subscription fees, advertisement slots and insurance coverage. The target market for Panic Button App was defined by considering the extent of smartphone and internet usage and intersecting the number with facts regarding high risk and emergency related incidents. To ensure that users will continue to patronize the application, a roadmap was defined to add more features. The roadmap includes integration with government agencies and partnerships with private entities to enable more services for the application. To come with the proof-of-concept for the Panic Button App, the class used Project Management concepts learned in TM 291. The project scope and structure were identified first. Afterwards, the project manager came up with the work-breakdown structure and Gantt Chart. Costing was tracked by the designated CFO. The risk assessment, stakeholder analysis and communications plan were created under the supervision of the assistant project manager. Overall, the project was successful albeit with minor issues and some room for improvement. The paper is divided into two sections. The first section is all about the class concept and business plan. The second section is about the project management technology that was used in coming up with the proof of concept.
In partial fulfillment of the requirements in TM 291